Synthesis and SAR of novel capsazepine analogs with significant anti-cancer effects in multiple cancer types. Issue 1 (1st January 2019) - De La Chapa, Jorge; Valdez, Matthew; Ruiz, Franscisco; Gonzales, Keith; Mitchell, Wes; McHardy, Stanton F.; Hart, Matthew; Polusani, Srikanth R.; Gonzales, Cara B.
Graphical abstract: Abstract: We previously demonstrated that capsazepine (CPZ), a synthetic transient receptor potential Vanilloid subtype 1 (TRPV1) antagonist, has significant anti-cancer effects in vivo . The purpose of this study was to develop more potent analogs based upon CPZ pharmacophore and structure–activity relationships (SAR) across analogs. We generated 30 novel compounds and screened for their anti-proliferative effects in cultured HeLa cervical cancer cells. Cell viability assays identified multiple compounds with IC50s  < 15 μM and one compound, 29 with an IC50  < 5 μM; six fold more potent than CPZ. We validated the anti-proliferative efficacy of two lead compounds, 17 and29, in vivo using HeLa-derived xenografts in athymic nude mice. Both analogs significantly reduced tumor volumes by day 8 compared to control treated animals (p < 0.001) with no observable adverse effects. Calcium imaging determined that compound17 activates TRPV1 whereas29 neither activates nor inhibits TRPV1; indicating a unique mechanism-of-action that does not involve TRPV1 signaling. Cell viability assays using a panel of additional tumor types including oral squamous cell carcinoma, non-small cell lung cancer (NSCLC), breast cancer, and prostate cancer cell lines (HSC-3, H460, MDA-231, and PC-3 respectively) demonstrated that both lead compounds were efficacious against every cancer type tested. Compounds29 displayed IC50s of 1–2.5 μM in HSC-3and PC-3cells. Thus, we propose that these novel CPZ analogs may serve as efficacious therapeutic agents against multiple tumor types that warrant further development for clinical application.